2016
DOI: 10.1007/s12192-016-0704-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise cold water immersion does not alter high intensity interval training-induced exercise performance and Hsp72 responses, but enhances mitochondrial markers

Abstract: This study aims to evaluate the effect of regular post-exercise cold water immersion (CWI) on intramuscular markers of cellular stress response and signaling molecules related to mitochondria biogenesis and exercise performance after 4 weeks of high intensity interval training (HIIT). Seventeen healthy subjects were allocated into two groups: control (CON, n = 9) or CWI (n = 8). Each HIIT session consisted of 8-12 cycling exercise stimuli (90-110 % of peak power) for 60 s followed by 75 s of active recovery th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
3
20
1
1
Order By: Relevance
“…Despite increases in P peak and TT 20 mean power, regular post-exercise WBC during 4 weeks of HIT had no significant effect on improvements in these markers of endurance performance, nor T max or W Tmax . This is consistent with the reported effects of regular CWI on cycling performance 31,32 , and thus supports the notion that regular cryotherapy during an endurance exercise training period has limited effect on augmenting training-induced changes in aerobic adaptations 25 . In the current study, the large (but not significant) differences between conditions following training for T max (3.9% for CON vs .…”
Section: Discussionsupporting
confidence: 90%
“…Despite increases in P peak and TT 20 mean power, regular post-exercise WBC during 4 weeks of HIT had no significant effect on improvements in these markers of endurance performance, nor T max or W Tmax . This is consistent with the reported effects of regular CWI on cycling performance 31,32 , and thus supports the notion that regular cryotherapy during an endurance exercise training period has limited effect on augmenting training-induced changes in aerobic adaptations 25 . In the current study, the large (but not significant) differences between conditions following training for T max (3.9% for CON vs .…”
Section: Discussionsupporting
confidence: 90%
“…However, Lindsay et al ( 2016 ) showed that repeated CWI applied to mixed martial artists during a training camp attenuated the inflammatory response, but did not affect measures of performance. Repeated CWI applied after high intensity interval training (HIIT) or a combination of HIIT with low-moderate intensity aerobic exercise also does not influence indices of performance or muscle cellular signaling (Halson et al, 2014 ; Aguiar et al, 2016 ; Christiansen et al, 2018 ). Although these studies represent only a small proportion of published CWI research, they do demonstrate the complexity in understanding the value of this recovery intervention.…”
Section: A Brief History Of Cwi Researchmentioning
confidence: 99%
“…Accordingly, a future research direction should investigate normal, scheduled training in the morning with subsequent cold exposures in the late afternoon or evening once recovery from the exercise has largely been facilitated. This method has potential additional benefits of improving sleep quality [ 166 ] and providing a reduction in thermal strain during ensuing exercise bouts [ 167 ], with some data showing that cold-water immersion following high-intensity interval training in the heat is able to further increase gene transcripts allied to mitochondrial biogenesis and the HSP response [ 168 ]. There is potential for cold-water immersions to ‘blunt’ training adaptation, however this appears more relevant to resistance training paradigms [ 169 , 170 ], when implemented immediately post-exercise [ 171 ], a modality that is highly unlikely to be used for cross-adaptation.…”
Section: Cold To Hypoxia Cross-adaptationmentioning
confidence: 99%